2012
DOI: 10.1111/j.1468-1331.2012.03795.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of chronic and episodic migraine in children and adolescents

Abstract: Our results showed that CM is an important cause of headache in both children and adolescents with some defining headache characteristics and risk factors concentrated in different age-groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…During this analysis we showed an important effect of unilateral pain localization on migraine with atopic disorders comorbidity. The unilateral headache localization and the throbbing headache quality of ETTH sufferers' support the possible transforming characteristics of ETTH to migraine in this age group, as mentioned previously in our epidemiological study …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…During this analysis we showed an important effect of unilateral pain localization on migraine with atopic disorders comorbidity. The unilateral headache localization and the throbbing headache quality of ETTH sufferers' support the possible transforming characteristics of ETTH to migraine in this age group, as mentioned previously in our epidemiological study …”
Section: Discussionsupporting
confidence: 87%
“…A large‐scale population‐based cross‐sectional study (The Head‐HUNT Study) has confirmed that migraine is associated with respiratory and allergic disorders and these data are supported by other previous reports . Episodic tension type headache (ETTH) is a frequent headache subtype in children and adolescents that shares some pathophysiological mechanism with migraine and is a potential transforming risk factor for migraine in adulthood and vice versa . ETTH sufferers reported some atopic disorder comorbidities in an adult age group but there was a lower ratio than in a migraine subgroup …”
supporting
confidence: 72%
“…15 Ozge A et al in their school-based study found that the prevalence of migraine increases with increasing age. 5 The significant risk factors for the development of migraine include adolescent age, female gender and father and sibling headache histories.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated overall mean prevalence of headache was 54.4 % and the overall mean prevalence of migraine was 9.1 % [7]. Totally, 10.4 % of the children, predominantly the girls, received the diagnosis of migraine when they grew older [8]. Indeed, it is well known that children frequently change their headache prevalence and characteristics, and even the type of headache shows important changes in the course of the adolescence and adulthood, independently from the use of either pharmacological or behavioural treatment or both.…”
Section: Epidemiologymentioning
confidence: 98%